Pemerolehan PEMEROLEHAN BAHASA PERTAMA ANAK USIA 2,2 TAHUN DALAM TATARAN SINTAKSIS - Nurtati Muharomah (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
This study aims to determine the acquisition of language spoken by children and describe the process of language pronunciation in a syntactic level. The research subject was a 2,2 year old child named Zaynaya Lulu Ajmalia whose parents are Sundanese. The method in this research is descriptive qualitative. Describing the qualitative methodology resulted in data in the form of spoken words which were transcribed. The data collection technique uses the method with interview techniques, recording the words spoken by the child. Based on Naya's research, she has been able to pronounce one word utterances (USK), two-word utterances (UDK), a series of words that form interrogative, declarative, and imperative sentences. Naya produced more declarative sentences of 9 sentences. Naya's acquisition of language is influenced by the parents' first language, namely Sundanese. Naya, who in her speech includes Sundanese vocabulary. Keyword: acquisition of language, first language, syntax